PARTISIPASI KELOMPOK TANI DALAM MENDUKUNG PROGRAM-PROGRAM PERTANIAN BERKELANJUTAN DI KECAMATAN PURING, KABUPATEN KEBUMEN (STUDI KOMPARASI KELOMPOK TANI KELAS LANJUT DAN PEMULA) - Oneng Sunaringtyas Puspitaningsih; Bekti Wahyu Utami; Arip Wijianto (Caraka Tani: Journal of Sustainable Agriculture, 2016)
This research aimed to assess the participation of members of farmer groups in Puring, Kebumen regency, and to compare the participation of members of farmer groups in advanced classes and beginner classes in Puring, Kebumen regency.. Through this research, farmer groups are expected to maintain the participation of each member so that the farmer groups to be effective, optimal and can achieve a higher grade category. Research location determined by purposive in Puring, Kebumen regency. Method of sampling determined by multistage cluster random sampling. To determine whether there are differences in the participation and effectiveness of farmer Group in advanced classes and beginner classes used by Man-Whitney Test From the Mann-Whitney U test, can be seen in all statistical Test output indicator for the level of participation  and effectiveness has a small z value and sig. 2-tailednya greater than 0.005. It states the test results are not statistically significant, thus the hypothesis is accepted that there is no difference in the distribution of scores on the level of participation in the advanced classes and beginner classes.